Insectos y ácaros de la yuca y su control - Bellotti, Anthony C.; Reyes Q., Jesús Antonio; Arias V., Bernardo; Vargas H., Octavio (International Center for Tropical Agriculture, 1979)
Insects and mites that attack cassava are described and grouped according to the part of the plant affected, and some control measures are given: (1) Insects that attack planting material: scale insects (Aonidomytilus albus), fruit flies (Anastrepha spp.) and stemborers (Coleoptera). (2) Cuttings and seedling damage: white grubs (Leucopholis rorida and Phyllophaga sp.), cutworms (Agrotis ipsilon and Prodenia eridania), termites (Coptotermes spp.) and crickets (Gryllus assimilis and Gryllotalpa sp.). (3) Insects and mites that attack the aerial part: (a) leaf-eating insects: cassava hornworm (Erinnyis ello), leaf-cutting ants (Atta sp. and Acromyrmex sp.); (b) mites and piercing insects: mites (Tetranychus urticae, Oligonychus peruvianus and Mononychellus tanajoa), cassava lace bug (Vatiga manihotae) and whiteflies (Aleyrodidae); (c) rasping insects: thrips (Frankliniella williamsi); (d) insects that attack stems: shoot flies (Silba pendula, Carpolonchaea chalybea), fruit flies and stemborers; (e) leaf deformers: gall midges (Iatrophobia brasiliensis); (f) insects that attack the external stem: scale insects and mealybugs (Phenacoccus spp.). (4) Storage pests of dried cassava (Stegobium paniceum, Araecerus fasciculatus, Rhizopertha dominica, Dinoderus minutus, Tribolium casteneum and Latheticus oryzae). Finally, it is concluded that integrated pest control in cassava should be based on the interaction of biological control, var. resistance and cultural practices. (CIAT)